1992
DOI: 10.1016/0014-5793(92)81253-i
|View full text |Cite
|
Sign up to set email alerts
|

Structure/function analyses of human sex hormone‐binding globulin by site‐directed mutagenesis

Abstract: Human sex hormone-binding globulin (hSHBG) and rat androgen-binding protein (rABP) exhibit distinct afilnities for sex-steroids. We therefore constructed and expressed a hSHBG/rABP hybrid cDNA encoding the N-terminal portion of hSHBG (205 residues) and the C-terminal portion of rABP (168 residues). The resulting chimera displayed similar steroid-binding characteristics as hSHBG and was recogniscd by a monoclonal antibody (SlB5) for hSHBG. We then created substitutions at Ser-133, His-136 and Met-139. The Asp-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
5
17
0
Order By: Relevance
“…Site-directed mutagenesis experiments (24)(25)(26)(27) have confirmed the importance of the Met-139 residue for steroid binding by human SHBG and have demonstrated that the steroid-binding site is mainly situated within the Leu-1-Glu-205 portion of human SHBG which comprises the above-described sites of affinity labeling.…”
mentioning
confidence: 69%
“…Site-directed mutagenesis experiments (24)(25)(26)(27) have confirmed the importance of the Met-139 residue for steroid binding by human SHBG and have demonstrated that the steroid-binding site is mainly situated within the Leu-1-Glu-205 portion of human SHBG which comprises the above-described sites of affinity labeling.…”
mentioning
confidence: 69%
“…A human SHBG cDNA in the pSELECT-1 vector (Promega) was mutated using an oligonucleotide primer (according to the protocol provided by Promega) to introduce a BamHI site immediately 5' to the codon for Leu-1 in the mature polypeptide (Hammond et al, 1987;Bocchinfuso et al, 1992b). The resulting cDNA was then excised with BamHI and inserted into a BamHI-digested pGEX-2T vector (Pharmacia) to create a cDNA that encodes a GST/SHBG fusion protein, designated SHBG( 1-373) as shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This question arises because, as we shall review, it is clear that SHBG is synthesized in these two tissues. Two major SHBG transcripts are known, each originating from a different promoter (minor SHBG transcripts have received little attention and will not be discussed here) (Gershagen et al 1987, 1989, 1991, Hammond et al 1987, 1989, Joseph et al 1991, Bocchinfuso et al 1992, Bocchinfuso & Hammond 1994, Hammond & Bocchinfuso 1996, Janne et al 1998. The first major transcript encodes a precursor for the secreted (plasma) form of SHBG, and was originally described in the liver (SHBG L ) (Que & Petra 1987), while the second encodes a protein of unknown function and was originally described in the testis (SHBG T ) (Hammond et al 1989).…”
Section: The Sex Hormone-binding Globulin (Shbg) Genementioning
confidence: 99%